Analisis Penentuan Lokasi Tempat Pembuangan Akhir Di Kota Tidore Kepulauan - Buyung Faisal; Rudi Latief; Idris Taking (Journal of Urban Planning Studies, 2022)
The purpose of this research is to find out locations that have the potential to be used as landfill sites in the City of Tidore Islands with the applicable provisions or have been set "SNI 19-3241-1994", and also to know the characteristics of the landfill land in terms of geology, hydrology, topography, slope, rainfall in the City of Tidore Islands. Based on this research, there are 5 locations that have the potential or are feasible as landfills in the City of Tidore Islands in accordance with SNI 19-3241-1994, which are very suitable to be used as landfill locations, which are divided into 2 classes, namely the location of class I is in Kel . Guraping, North Oba District, Kaiyasa Village, North Oba District, Togome Village, Central Oba District, and Siokona Village, Central Oba District. Land characteristics of the "TPA" Garbage Disposal Site in the City of Tidore Islands from a geological point of view itself is not in the geological hazard zone